Correlation and path coefficient analysis in pointed gourd (Bangladesh Journal of Agricultural Research, 2007)
Correlation studies in 25 genotypes of pointed gourd revealed that fruit yield had a positive correlation with vines per plant and fruits per plant. In general, genotypic correlation coefficients were higher than the corresponding phenotypic correlation coefficients suggesting that the environmental influence reduces the relationship between yield and yield contributing characters of pointed gourd. Path coefficient analysis showed that fruits per plant had direct positive effects on fruit yield. This indicates that this character was the major contributor to fruit yield. Therefore, maximum weightage should be given to this character for improvement of yield in pointed gourd. Bangladesh J. Agril. Res. 32(2) 2007: 261-268.